Pengaruh Kualitas Pelayanan, Brand Image, Kualitas Website Terhadap Kepuasan Pelanggan Lazada (Studi Pada Mahasiswa USNI Fakultas Ekonomi) - Agus Wahyono; R.M Septian Muchsin (Jurnal Manajemen, 2018)
This study aims to determine the effect of Service Quality, Brand Image and Website Quality toward Customer Satisfaction. The method used in this study was quantitative method and assessment of the results of this study based on the answers on questionnaires which was given to respondents using Likert Scale. Populations in this research were USNI students from the Faculty of Economics and the total samples in this research were 100 respondents. The analytical methods used in this study are descriptive analysis, instrument test (Validity and Normality), Classic Assumption Test (Normality, Heteroscedasticity, Multicolonierity and Autocorrelation), Multiple Linear Regression Analysis, T Test, F Test and Determinant R² coefficient . From the result of t test (partially), it had been obtained the result that variable of Service Quality (X1) and Brand Image (X2) had influence and significant toward Customer Satisfaction of Lazada Online store. While the variable of Website Quality (X3) had no effect and not significant toward Customer Satisfaction of Lazada Online store. From the f test (simultaneously), obtained the result that the three variables had an effect and significant toward the Customer Satisfaction of Lazada online store.